2006
DOI: 10.1128/mcb.00161-06
|View full text |Cite
|
Sign up to set email alerts
|

Control of Translocations between Highly Diverged Genes by Sgs1, the Saccharomyces cerevisiae Homolog of the Bloom'sSyndrome Protein

Abstract: Sgs1 is a RecQ family DNA helicase required for genome stability in Saccharomyces cerevisiae whose human homologs BLM, WRN, and RECQL4 are mutated in Bloom's, Werner, and Rothmund Thomson syndromes, respectively. Sgs1 and mismatch repair (MMR) are inhibitors of recombination between similar but divergent (homeologous) DNA sequences. Here we show that SGS1, but not MMR, is critical for suppressing spontaneous, recurring translocations between diverged genes in cells with mutations in the genes encoding the chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 107 publications
5
88
0
Order By: Relevance
“…The Sgs1p helicase has been implicated in many processes of DNA metabolism, including regulation of homologous recombination, suppression of crossing over in vegetative cells (Ira et al 2003), and prevention of aberrant crossing over during meiosis (Oh et al 2007). Also, Sgs1p suppresses homeologous recombination (Myung et al 2001;Spell and Jinks-Robertson 2004), and deletion of SGS1 leads to increased translocations between divergent DNA sequences that share only limited homology (Schmidt et al 2006). The latter function of Sgs1p could explain the increased GC observed in our experimental system.…”
Section: Leumentioning
confidence: 66%
“…The Sgs1p helicase has been implicated in many processes of DNA metabolism, including regulation of homologous recombination, suppression of crossing over in vegetative cells (Ira et al 2003), and prevention of aberrant crossing over during meiosis (Oh et al 2007). Also, Sgs1p suppresses homeologous recombination (Myung et al 2001;Spell and Jinks-Robertson 2004), and deletion of SGS1 leads to increased translocations between divergent DNA sequences that share only limited homology (Schmidt et al 2006). The latter function of Sgs1p could explain the increased GC observed in our experimental system.…”
Section: Leumentioning
confidence: 66%
“…An unusual class of translocations is detected between highly diverged sequences in the absence of the Sgs1 helicase and at least one other protein involved either in the DNA damage checkpoint response, chromatin assembly or the DNA unwinding. 38 Again, many of these translocations were complex because the initial event resulted in formation of dicentric chromosome that underwent a secondary rearrangement to form a stable product. These rearrangements between the diverged CAN1, LYP1 and ALP1 genes were dependent on RAD52 and partially dependent on RAD51, and the breakpoints were primarily within blocks of greatest sequence identity.…”
Section: Bir and Gcrsmentioning
confidence: 99%
“…Several studies using this approach have demonstrated that there are eight pathways for suppressing these chromosomal aberrations, while six pathways promote GCR formation. The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%